Oral Porphyromonas gingivalis and Fusobacterium nucleatum Abundance in Subjects in Primary and Secondary Cardiovascular Prevention, with or without Heterozygous Familial Hypercholesterolemia - Maria Cristina Curia; Pamela Pignatelli; Domenica Lucia D’Antonio; Damiano D’Ardes; Elena Olmastroni; Luca Scorpiglione; Francesco Cipollone; Alberico Luigi Catapano; Adriano Piattelli; Marco Bucci; Paolo Magni (Biomedicines, 2022)
Background: Low-grade chronic inflammation, promoted by dysbiosis of the gut and oral microbiota, has been shown to contribute to individual susceptibility to atherosclerotic cardiovascular disease (ASCVD). High oral Porphyromonas gingivalis (Pg) and lower Fusobacterium nucleatum (Fn) concentrations have been associated with clinical and experimental atherosclerosis. We assessed oral Pg and Fn abundance in very high-risk patients with previously diagnosed ASCVD, with or without heterozygous familial hypercholesterolemia (HeFH), in subjects with HeFH in primary prevention and in healthy subjects. Methods: In this cross-sectional study, 40 patients with previously diagnosed ASCVD (10 with genetically proven HeFH, and 30 without FH), 26 subjects with HeFH in primary prevention, and 31 healthy subjects were selected to quantify oral Pg and Fn abundance by qPCR and assess oral health status. Results: Compared to healthy subjects, patients with previously diagnosed ASCVD showed greater Pg abundance (1101.3 vs. 192.4, p = 0.03), but similar Fn abundance. HeFH patients with ASCVD had an even greater Pg abundance than did non-HeFH patients and healthy subjects (1770.6 vs. 758.4 vs. 192.4, respectively; p = 0.048). No differences were found in the levels of Pg and Fn abundance in HeFH subjects in primary prevention, as compared to healthy subjects. Conclusions: Greater oral Pg abundance is present in very high-risk patients with previously diagnosed ASCVD, with or without FH, suggesting a potential relationship with CV events. Future studies will assess the predictive value of Pg abundance measurement in ASCVD risk stratification.